Solar power plant 618.8 kWp monitoring correction on the Fusion application - Hutauruk, Sindak; Siagian, Pandapotan; Sitinjak, Reinhard A. (Institute of Advanced Engineering and Science, 2024)
Monitoring of energy produced by the solar power plant (SPP) with a capacity of 618.8 kWp at HKBP Nommensen University in Medan is carried out using the FusionSolar application. This SPP energy management application includes displaying yield, energy consumption, energy exports, and SPP energy imports. The amount of energy displayed using the FusionSolar application is compared with the amount of energy resulting from manual calculations based on power data displayed on the alternating current (AC) combiner panel from 3-phase inverters. This comparison was carried out over seven days of measurements. It produced an average difference of 5.779%, with a correction value of 0.942, so the energy reading resulting from the FusionSolar application must be multiplied by this correction value.